2007
DOI: 10.1002/hyp.6593
|View full text |Cite
|
Sign up to set email alerts
|

The effect of terrace geology on ground‐water movement and on the interaction of ground water and surface water on a mountainside near Mirror Lake, New Hampshire, USA

Abstract: Abstract:The west watershed of Mirror Lake in the White Mountains of New Hampshire contains several terraces that are at different altitudes and have different geologic compositions. The lowest terrace (FSE) has 5 m of sand overlying 9 m of till. The two next successively higher terraces (FS2 and FS1) consist entirely of sand and have maximum thicknesses of about 7 m. A fourth, and highest, terrace (FS3) lies in the north-west watershed directly adjacent to the west watershed. This highest terrace has 2 m of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…These locations were not related to the gully/ridge features in the catchment, in conflict with our prior hypothesis, but instead may indicate preferential groundwater flow paths which channel water from the upper slopes. Such preferential paths were previously reported at Maimai catchment where there is a clearly defined soil-bedrock interface Woods and Rowe, 1996); our results suggest a similar outcome in the Langs Gully catchment despite the gradual transition from soil to broken bedrock. The cross-slope gradients needed to generate the preferential paths could be caused by deeper bedrock structures, or by local areas with high permeability such as the gravel-rich soil layers observed during installation of the soil moisture sensors.…”
Section: Wet-period Variability Caused By Partial Saturation and Grousupporting
confidence: 90%
See 3 more Smart Citations
“…These locations were not related to the gully/ridge features in the catchment, in conflict with our prior hypothesis, but instead may indicate preferential groundwater flow paths which channel water from the upper slopes. Such preferential paths were previously reported at Maimai catchment where there is a clearly defined soil-bedrock interface Woods and Rowe, 1996); our results suggest a similar outcome in the Langs Gully catchment despite the gradual transition from soil to broken bedrock. The cross-slope gradients needed to generate the preferential paths could be caused by deeper bedrock structures, or by local areas with high permeability such as the gravel-rich soil layers observed during installation of the soil moisture sensors.…”
Section: Wet-period Variability Caused By Partial Saturation and Grousupporting
confidence: 90%
“…Winter et al (2008) and Tiedeman et al (1998) monitored 31 bedrock wells and found water table gradients caused by different geological units within a catchment. Even in headwater catchments, variability in groundwater dynamics has been found due to multiple underlying aquifers (Kosugi et al, 2008(Kosugi et al, , 2011.…”
Section: Groundwater Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Las zonas de interacción entre las aguas subterráneas y superficiales presentan características físico-químicas específicas que afectan a la hidrología, la ecología y a los procesos biogeoquí-micos del nitrógeno. Winter et al (2008) vieron que el agua subterránea presentaba condiciones anóxicas y una composición química diferente al atravesar el cauce de un arroyo e interaccionar con los materiales del lecho. Desde un punto de vista ecológico, la presencia de microalgas bentónicas puede estimular la nitrificación durante el día y la desnitrificación durante la noche (Groffman et al 2009).…”
Section: Impactos En El Agua Superficial De Arroyos Lagos Y Humedalesunclassified